Myśleć fantastyką. Przez science fiction do posthumanizmu - Gajewska, Grażyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The author presents the thesis that fantastic literature and film, especially in the science fiction variant, is a privileged form of expression in posthumanist discourse. The themes, motifs and protagonists of science fiction are invoked in various contexts by Donna J. Haraway, Rosi Braidotti, Luciana Parisi, and Pramod K. Nayar. The author analyzes various areas of the involvement and usage of science fiction in posthumanist discourse: on the ontological, axiological and epistemological levels.